Father Brown. Complete season eleven [videorecording (DVD)] - Flowerday, Rachel (Screenwriter); Guner, Tahsin, 1972- (BBC Studios, 2024)
It's now 1955 and Chief Inspector Sullivan and Mrs. Devine have grown closer since we saw them last, something that hasn't escaped the notice of Father Brown and Brenda. With a food fayre to die for, a real-life crime at a crime writing festival and a village rivalry that turns deadly, there's plenty for the gang to be busy with. And when his old friend Sister Boniface is implicated in a murder at an arts and craft fair, Father Brown must prove her innocence, before it's too late.